Cleavage of the N≡N Triple Bond and Unpredicted Formation of the Cyclic 1, 3‐Diaza‐2, 4‐Diborete (FB)2N2 from N2 and Fluoroborylene BF. (26th June 2021) - Xu, Bing; Beckers, Helmut; Ye, Haoyu; Lu, Yan; Cheng, Juanjuan; Wang, Xuefeng; Riedel, Sebastian
Abstract: A complete cleavage of the triple bond of N2 by fluoroborylene (:BF) was achieved in a low‐temperature N2 matrix by the formation of the four‐membered heterocycle FB( μ ‐N)2 BF, which lacks a trans ‐annular N−N bond. Additionally, the linear complex FB=N−N=BF and cyclic FB( η 2 ‐N2 ) were formed. These novel species were characterized by their matrix infrared spectra and quantum‐chemical calculations. The puckered four‐membered‐ring B2 N2 complex shows a delocalized aromatic two‐electron π‐system in conjugation with the exo ‐cyclic fluorine π lone pairs. This work may contribute to a rational design of catalysts based on borylene for artificial dinitrogen activation. Abstract : The four‐membered heterocycle FB( μ ‐N)2 BF is obtained from fluoroborylene, FB, and N2 . It shows a complete cleavage of the N2 triple bond and a delocalized aromatic two‐electron π‐bond conjugated with the exo ‐cyclic fluorine π lone pairs, indicating the importance of fluorine‐specific interactions.